State of the art and new perspectives in non-invasive glucose sensors - Losoya-Leal, A.; Camacho-León, S.; Dieck-Assad, G.; Martínez-Chapa, S. O. (Revista Mexicana de Ingenieria Biomedica, 2012)
Self-monitoring of blood glucose levels provides diabetic patients with a prompt method of measuring their blood glucose concentration, as opposed to conventional laboratory measurements. Frequent testing aids patients in the prevention and detection of hyper or hypoglycemia events. Only invasive and minimally invasive glucose sensors are currently commercially available. However, during the last couple of decades, work towards the development of a non-invasive glucose monitor has increased significantly among research groups with motivating results. Many techniques have been studied and implemented, each with their particular advantages and challenges. This paper presents a qualitative review of different technologies of non-invasive glucose sensors: spectroscopy-based methods, transdermal extraction-based methods, fluorescence, electromagnetic variations and polarimetry. This study identifies strengths and opportunities of currently available glucose monitoring techniques, as well as main characteristics and performance variables for an ideal non-invasive monitor. The most promising approaches towards the development of a truly non-invasive and clinically accurate glucose sensor are discussed.